Tales of the Old Gamekeepers. - Martin, Brian P (Newton Abbott David & Charles, 1992)
Combining the anecdotes of the living and the recorded stories of the dead, this book is a study of the professional gamekeeper. The author has also written "Sporting Birds of the British Isles" and is on the editorial staff of "Shooting Times and Country Magazine
Include colored Illustrtion, Indexes
Keywords: Great Britain -- Game protection -- Gamekeepers